数学2次根式化简[x^2-x-2+(x-1)sqrt(x^2-4)]/[x^2+x-2+(x+1)sqrt(x^2-4)] (x大于2)

来源:学生作业帮助网 编辑:作业帮 时间:2021/06/25 19:02:19

数学2次根式化简[x^2-x-2+(x-1)sqrt(x^2-4)]/[x^2+x-2+(x+1)sqrt(x^2-4)] (x大于2)
数学2次根式化简
[x^2-x-2+(x-1)sqrt(x^2-4)]/[x^2+x-2+(x+1)sqrt(x^2-4)] (x大于2)

数学2次根式化简[x^2-x-2+(x-1)sqrt(x^2-4)]/[x^2+x-2+(x+1)sqrt(x^2-4)] (x大于2)
原式=[(x-2)(x+1)+(x-1)sqrt(x+2)sqrt(x-2)]/[(x+2)(x-1)+(x+1)sqrt(x+2)sqrt(x-2)]
={sqrt(x-2)[(x+1)sqrt(x-2)+(x-1)sqrt(x+2)]}/{sqrt(x+2)[(x-1)sqrt(x+2)+(x+1)sqrt(x-2)]}
=sqrt(x-2)/sqrt(x+2)
=sqrt[(x-2)/(x+2)]